Challenges on the epidemiological and economic burden of diabetes and hypertension in Mexico - Armando Arredondo; Emanuel Orozco; Jaqueline Alcalde-Rabanal; Juan Navarro; Alejandra Azar (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze the epidemiological and economic burden of the health services demand due to diabetes and hypertension in Mexico. METHODS Evaluation study based on a time series study that had as a universe of study the assured and uninsured population that demands health services from the three main institutions of the Health System in Mexico: The Health Department, the Mexican Institute of Social Security, and Institute of Services and Social Security for State Workers. The financing method was based on instrumentation and consensus techniques for medium case management. In order to estimate the epidemiological changes and financial requirements, a time series of observed cases for diabetes and hypertension 1994-2013 was integrated. Probabilistic models were developed based on the Box-Jenkins technique for the period of 2013-2018 with 95% confidence intervals and p < 0.05. RESULTS Comparing results from 2013 versus 2018, in the five regions, different incremental trends of 14%-17% in epidemiological changes and 58%-66% in the economic burden for both diseases were observed. CONCLUSIONS If the risk factors and the different models of care remained as they currently are in the three institutions analyzed, the financial consequences would be of greater impact for the Mexican Institute of Social Security, following in order of importance the Institute of Services and Social Security for State Workers and lastly the Health Department. The financial needs for both diseases will represent approximately 13%-15% of the total budget allocated to the uninsured population and 15%-17% for the population insured depending on the region.